The panoply of the armoured personage from the capital from Bisotun. Remarks on the spread of the military technology along the Silk Road - Skupniewicz, Patryk (Acta Archaeologica Lodziensia, 2022)
The armour of the personage depicted on the capital from Bisotun, exhibited in Ṭāq-e Bostān, has been an object of the research already several times with no definite setting in typology of arms and armour and allocation in historical trends. The article attempts to fill this gap. The article defines the helmet as lamellar/laminar type with the splints with ornately incised edges and central splint over the personage’s nose. The top of the dome is crowned by the decorative, solid finial to which a korymbos is attached. This relates the helmet to the lamellar helmets from Xinjiang and Tang Dynasty China rather than to [?] earlier Kushan lamellar helmets and related Eurasian types, characterised by a flat, round sheet at the top of the dome, usually a sheet over the face, often with a nasal and the laminae running overlapping around the dome, without the central lamina over the face and other laminae spreading to its sides. The body armour can be described as a cuirass made of metallic stripes riveted to each other and placed horizontally, with the central, vertical stripe in front. The type is derived from Parthian predecessors with plausible earlier, Achaemenid and Hellenistic sources. The cuirass with frontal opening was a dominant type of construction among the Sasanian armours. The direct relation was evidenced with Korean and Japanese cuirasses of 3rd and 4th centuries (later replaced by lamellar coats) and Eurasian, mainly Xinjiang types.